Uma fotografia, múltiplas imagens: a educação rural no norte do Brasil One photograph, myriad images: rural education in Northern Brazil - Sonia Maria da Silva Araújo (História, Ciências, Saúde: Manguinhos, 2010)
Aborda os processos de constituição e institucionalização de escolas nas fazendas de criação extensiva localizadas na ilha de Marajó, interior de Soure, Brasil, e demonstra que eles ocorreram associados à grande propriedade e a relações políticas estabelecidas entre fazendeiros, vaqueiros e poder público. Refexões teóricas, dados sociais e acontecimentos somam-se a imagens fotográficas que revelam a fragilidade da educação pública oferecida às crianças das zonas rurais do extremo norte do país. The article addresses the processes by which schools have been established and institutionalized on extensive-grazing ranches in rural Soure, Marajó Island, Brazil. Emergence of these schools has been tied to large landholdings and to the political relations between ranchers, vaqueiros, and government. Theoretical reflections, social data, and events are placed side-by-side with photographs that depict the fragile state of public education available to children living in the rural areas of far northern Brazil.